(untitled) (Journal of Economic Research & Business Administration, 2016)
For support of small and medium-sized business in our country have given considerable attention. One of institutions, which support small and medium business in Kazakhstan is the Institute of business ombudsman. Many entrepreneurs of Kazakhstan are often faced with cases of violation of their rights and legal interests by government authorities. Small and medium-sized businesses with complaints are turning to the National Chamber of Entrepreneurs, which currently performs function of business ombudsman. April 29, 2015 President Nursultan Nazarbayev has been voiced by the Plan of the Nation. In terms of the Nation represented by 100 concrete steps which aimed to implement five institutional reforms. One of these steps is the «Strengthening of the Ombudsman institution for protection business interests of entrepreneurs.» The purpose of the study – business activities of the Ombudsman and his influence on the development of the private sector in our country, identify ways to strengthen this institution. Subject of research: the socio- economic relations of employers and the state institutions of Kazakhstan. The object of research is the defense of entrepreneurs by creating a business ombudsman.